Analysis of Preference Structure in Billie Eilish Hot Ones - Robbianto Ilham; Seliana Rohmatul Mawaddah; Afifah Al Rosyidah (STAI Nurul Islam Mojokerto, 2026)
Preference structures are important in the study of conversation since they offer an observable perspective into how human communication is governed by social rules. This study analyses the preference structure in the Hot Ones interview featuring Billie Eilish by applying the framework of Conversation Analysis (CA). It aims to find types of preference structure are found in the Hot Ones interview featuring Billie Eilish grounded in Yule (1996) concept of preference structure. This research serves as the first investigation to the Hot Ones interview featuring Billie Eilish analyse structural changes in a speaker's preferred and dispreferred responses while under the external factor of spicy food consumption in a public media interview. the data were taken from the interview transcript and examined using concepts of preferred and dispreferred response. The findings reveal that Billie Eilish frequently produces preferred responses in the form of direct agreements, minimal responses such as “yeah” or “right,” and affiliative laughter to maintain solidarity with the host. Dispreferred responses tend to appear with delays, hedges, doubt or added explanations to soften disagreement. All of these patterns show that in an informal media setting. How politeness and public image maintenance influence interaction between interviewer and the speaker.